Study of Plant Cordia Dichotoma as Green Corrosion Inhibitor for Mild Steel in Different Acid Media - R. Khandelwal; S. K. Arora; S. P. Mathur (E-Journal of Chemistry)
The corrosion inhibition of mild steel using extracts of Cordia dichotoma in different acid media was investigated by mass loss and thermometric methods. The experiments were carried out at 299±0.2 K in presence of different concentrations of dry fruit, leaves and stem extracts of Cordia dichotoma. The results reveal that the alcoholic extracts of Cordia dichotoma is a better corrosion inhibitor than that of toxic chemicals. The fruit extract is more potent than leaves and stem extracts to inhibit the corrosion rate. The study seeks to investigate the possibility of using extracts of Cordia dichotoma as a green corrosion inhibitor for mild steel.